Sergio Pitol e os disfarces da autobiografia - Rafael Gutiérrez (Estudos de Literatura Brasileira Contemporânea)
This article analizes the books of mexican writer Sergio Pitol (1933) El arte de la fuga (1997), El viaje (2000) and El mago de Viena (2005), included in Trilogía de la memoria (2007). These texts conform a literary autobiography created from a mixture of critic, road diaries and autobiographical narrative. The article analizes the way in which the writer tells his life through his readings and his creative process, the clues about his work that can be found in these texts, as well as the main characteristics and precedents of these hybrid contemporary forms.